The effect of asymmetrical V-bend on teeth and occlusal plane in growing patients with anterior crossbite - Neeranart Thirasupa (Prince of Songkla University, 2015)
Thesis (M.Sc. (Oral Health Sciences))--Prince of Songkla University, 2014